IMPLEMENTASI PROGRAM KELOMPOK USAHA BERSAMA (KUBE) DI DESA GUNUNG JAYA KECAMATAN DANGIA KABUPATEN KOLAKA TIMUR - Sari, Diana; Gunawan, Gunawan; Manguntara, La (Universitas Halu Oleo, 2020)
This research is descriptive qualitative research, with six informants in this study. Data collection techniques are direct observation and direct interviews. The data analysis used Data Reduction, Data Presentation, Draw Conclusions.The results of this study indicate that the KUBE Program is one of the Social Service strategies to empower poor families to increase their family income through business management. The implementation of the joint business group (KUBE) program in Gunung Jaya village can be seen in terms of the implementation of goals and objectives, training and assistance, financing and business management. Where in the implementation of the Joint Business Group program implementation in Gunung Jaya Village is less effective. This can be seen from the existence of several indicators of program implementation that are not running as it should, such as assistance, financing while in terms of objectives and targets and business management has been running effectively.Â